Physical-chemical characterization of the medicinal plant and extraction solution based on Clarisia racemosa for the development of an antimicrobial herbal medicine - Ventura, Thayline Ribeiro; Ribeiro, Pollyne Amorim Silva; Mendonça, Áquila Priscilla Ferreira de; Lima e Silva, Maria José Cristiane; Lima, Maria Joanellys dos Santos; Vilela, Williana Tôrres; Rolim Neto, Pedro José; Maria Ferreira da Silva, Rosali (Brazilian Journal of Implantology and Health Sciences, 2025)
Clarisia racemosa, popularly known as “Guariúba”, is a species of the Moraceae family, in Brazilian soils, this species can be found mainly in the Amazon rainforest. Currently, its commercialization is focused on the use of its wood in civil construction. Its chemical composition and therapeutic properties are still little studied in the literature. A study carried out previously, the C. racemosa species showed antimicrobial potential against gram-positive bacteria, especially Staphylococcus aureus. In this context, the aim of this work was to analyze the physicochemical characteristics of the pulverized plant drug obtained from the stem of C. racemosa and its ethanolic extract, for the future development of antimocrobial herbal medicines. In this context, the aim of this work was to analyze the physicochemical characteristics of the pulverized plant drug obtained from the stem of C. racemosa and its ethanolic extract, for the future development of antimocrobial herbal medicines. The ethanolic extract was obtained by maceration with 70% ethanol as the extracting solvent, after which pH, alcohol content, dry residue, density and phytochemical profile tests were carried out using thin layer chromatography. In the characterization of the plant drug, the powder was classified as semi-fine. The results of the ash content, foreign matter and moisture analysis were 0.82%, 0.002% and 7.13%, respectively. The ethanolic extract had the following values: density of 0.87g/mL, alcohol content of 71%, pH 5.93 and dry residue of 1.05%. Phytochemical prospecting revealed the presence of characteristic bands for cinnamic derivatives, condensed tannins and terpenes. In this way, this study evaluated the quality control parameters of the pulverized plant drug from the stem of C. racemosa, where the results were within the required parameters. The physicochemical tests contributed to the characterization of the plant drug and the extractive solution of C. racemosa, as well as to the future standardization of the dry extract, which met the standards required by the Brazilian Pharmacopoeia.